METHODOLOGICAL FRAMEWORK FOR OPTIMIZING INVESTMENT POLICY IN HOTEL INDUSTRY UNDER DIGITALIZATION CONDITIONS (European Journal of Interdisciplinary Research and Development, 2026)
The article explores the methodological improvement of investment policy in hotel enterprises under conditions of digital transformation and increasing market uncertainty. A comprehensive framework is proposed that integrates investment management with digital technologies, portfolio optimization principles, and data-driven decision-making tools. The study focuses on transforming traditional fragmented investment approaches into a unified digital investment ecosystem that enhances efficiency, transparency, and strategic alignment. The methodology combines system analysis, portfolio theory, and digital maturity assessment, enabling evaluation of both financial and non-financial effects of investment decisions. The results indicate that integration of investment policy with digital infrastructure (PMS, CRM, RMS, artificial intelligence, and analytics systems) significantly improves profitability, operational efficiency, and customer experience. The proposed Digital Investment Strategy model introduces a hybrid evaluation system including classical financial indicators (NPV, IRR, ROI, payback period) and a Digital Impact Index reflecting technological contribution. The findings confirm that digital-oriented investment policy increases return on investment, reduces operational costs, and strengthens long-term competitiveness in the hospitality sector